2021
DOI: 10.3390/life11080767
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and the Neurovascular Unit

Abstract: The neurovascular unit (NVU) is a relatively recent concept that clearly describes the relationship between brain cells and their blood vessels. The components of the NVU, comprising different types of cells, are so interrelated and associated with each other that they are considered as a single functioning unit. For this reason, even slight disturbances in the NVU could severely affect brain homeostasis and health. In this review, we aim to describe the current state of knowledge concerning the role of oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 196 publications
1
40
0
Order By: Relevance
“…Systemic, endocrine, neural factor, and oxidative stress disorders of the neurovascular unit (NVU) can contribute to the development of a brain injury, and play a major role in dysregulation, neuroinflammation, and neurodegeneration after a stroke. Complex communication and cell-to-cell communication is essential [ 10 , 11 ]; for example, pericyte modulators, such as the NADPH oxidase Nox4 (reactive oxygen species (ROS)), are significantly increased under hypoxic conditions, increasing MMP-9 and possibly increasing the size of the infarct area by playing a harmful role in the acute phase of ischemic stroke [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic, endocrine, neural factor, and oxidative stress disorders of the neurovascular unit (NVU) can contribute to the development of a brain injury, and play a major role in dysregulation, neuroinflammation, and neurodegeneration after a stroke. Complex communication and cell-to-cell communication is essential [ 10 , 11 ]; for example, pericyte modulators, such as the NADPH oxidase Nox4 (reactive oxygen species (ROS)), are significantly increased under hypoxic conditions, increasing MMP-9 and possibly increasing the size of the infarct area by playing a harmful role in the acute phase of ischemic stroke [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia can be a trigger for the impairment of neurovascular units via intracellular excess glucose flux followed by overproduction of reactive oxygen species (ROS) and advanced glycation-end products (AGEs) [51]. AGEs can be sources for ROS production and ROS is associated with mitochondrial dysfunction, resulting in the disturbance of the blood barrier function and the impairment of neuronal tissue homeostasis [52]. However, it was recently reported that microglia to be members of the neurovascular unit.…”
Section: Pathogenesis Of the Diabetic Retinopathy: The Impairment Of The Neurovascular Unitmentioning
confidence: 99%
“…Oxidative stress including overproduction of ROS results in ER stress related cell death or pyroptosis (Figure 3) and noncoding RNAs are involved in alteration of ROS homeostasis induced by oxidative stress [52]. Oxidative stress induces the alteration of several transcription factors such as AP-1, p53, or NF-κB which are involved in immune response, growth factor signaling, and neurodegeneration [52]. These possible involvements of epigenetic mechanisms induced by oxidative stress are also important, but go beyond the scope of this review.…”
Section: Mechanisms Of Neuronal Cell Death In Rgc Neuropathy In Diabetic Retinamentioning
confidence: 99%
“…In the diabetic retina, the interdependence between different cell types consisting of the NVUs is impeded by many stresses, including the polyol pathway [ 36 ], the hexosamine pathway [ 37 ], oxidative stress [ 38 , 39 ], protein kinase C (PKC) [ 40 , 41 ], advanced glycation-end products (AGEs) [ 42 ], and inflammation [ 43 ]. The hypothetic scheme of the neurovascular impairments provoked by these stresses in diabetic retinopathy is shown in Figure 1 .…”
Section: Physiology and Pathology Of Nvu In Diabetic Retinopathymentioning
confidence: 99%